A life of psalms in Jewish late antiquity - Berkovitz, Abraham Jacob (Jewish culture and contexts, 2023)
The Bible shaped nearly every aspect of Jewish life in the ancient world, from activities as obvious as attending synagogue to those which have lost their scriptural resonance in modernity, such as drinking water and uttering one’s last words. And within a scriptural universe, no work exerted more force than the Psalter, the most cherished text among all the books of the Hebrew Bible.A Life of Psalms in Jewish Late Antiquity clarifies the world of late ancient Judaism through the versatile and powerful lens of the Psalter. It asks a simple set of questions: Where did late ancient Jews encounter the Psalms? How did they engage with the work? And what meanings did they produce? A. J. Berkovitz answers these queries by reconstructing and contextualizing a diverse set of religious practices performed with and on the Psalter, such as handling a physical copy, reading from it, interpreting it exegetically, singing it as liturgy, invoking it as magic and reciting it as an act of piety. His book draws from and contributes to the fields of ancient Judaism, biblical reception, book history and the history of reading